Exome sequencing as first‐tier test for fetuses with severe central nervous system structural anomalies. (1st July 2022) - Yaron, Y.; Ofen Glassner, V.; Mory, A.; Zunz Henig, N.; Kurolap, A.; Bar Shira, A.; Brabbing Goldstein, D.; Marom, D.; Ben Sira, L.; Baris Feldman, H.; Malinger, G.; Krajden Haratz, K.; et al.
ABSTRACT: Objective: Prenatally detected central nervous system (CNS) anomalies present a diagnostic challenge. In this study, we compared the diagnostic yield of exome sequencing (ES) and chromosomal microarray analysis (CMA) in fetuses with a major CNS anomaly. Methods: This was a retrospective study of 114 cases referred for genetic evaluation following termination of pregnancy (TOP) due to a major CNS anomaly detected on prenatal ultrasound. All fetuses were first analyzed by CMA. All CMA‐negative cases were offered ES. CMA‐positive cases were reanalyzed using ES to assess its ability to detect copy‐number variants (CNVs). Results: CMA identified a pathogenic or likely pathogenic (P/LP) CNV in 11/114 (10%) cases. Eighty‐six CMA‐negative cases were analyzed using ES, which detected P/LP sequence variants in 38/86 (44%). Among recurrent cases (i.e. cases with a previously affected pregnancy), the incidence of P/LP sequence variants was non‐significantly higher compared with non‐recurrent ones (12/19 (63%) vs 26/67 (39%); P  = 0.06). Among the 38 cases with an ES diagnosis, 20 (53%) were inherited and carried a significant risk of recurrence. Reanalysis of 10 CMA‐positive cases by ES demonstrated that the bioinformatics pipeline used for sequence variant analysis also detected all P/LP CNVs, as well as three previously known non‐causative CNVs. Conclusions: In our study, ES provided a high diagnostic yield (> 50%) in fetuses with severe CNS structural anomalies, which may have been partly due to the highly selected case series that included post‐TOP cases from a specialist referral center. These data suggest that ES may be considered as a first‐tier test for the prenatal diagnosis of major fetal CNS anomalies, detecting both P/LP sequence variants and CNVs. This is of particular importance given the time constraints of an ongoing pregnancy and the risk of recurrence in future pregnancies. © 2022 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.